Antioxidant Bioactive Agents for Neuroprotection Against Perinatal Brain Injury - Virginia Beretta; Elena Scarpa; Silvia Carloni; Chiara Petrolini; Valentina Dell’Orto; Sebastiano Ravenda; Serafina Perrone (Cells)
Physiological oxidative stress plays a pivotal role in supporting proper growth and development. While moderate oxidative stress is essential for activating key metabolic pathways and maintaining normal cellular signaling, excessive production of reactive oxygen species (ROSs) can overwhelm the immature antioxidant systems of newborns, potentially leading to cellular damage and impaired physiological function. This vulnerability is particularly pronounced in the central nervous system, where limited detoxification capacity exacerbates the risk of oxidative damage, following hypoxic–ischemic events. Antioxidants agents—such as melatonin, erythropoietin, allopurinol, N-acetylcisteine, selenium, iminobiotin, taurine, and acetyl-L-carnitine—have demonstrated significant neuroprotective effects in preclinical experimental studies, reducing markers of oxidative injury and improving neurological outcomes. These neuroprotective agents have also been evaluated in clinical trials, demonstrating antioxidant effects. A major issue lies in the complexity of neurological damage, which is not associated with a single pathological pathway. Additionally, the inability of these agents to reach effective concentrations within the central nervous system, along with inconsistencies across clinical trials in terms of dosage and administration methods, hinders the ability to obtain robust results. Future efforts should therefore focus on the development of delivery systems capable of crossing the blood–brain barrier and on establishing standardized clinical trial protocols and study designs. This educational review aims to provide a comprehensive overview of emerging protective strategies, including antioxidant bioactive agents and nutritional interventions. It also explores the underlying mechanisms of oxidative stress and its impact on neonatal brain injury.